PERGESERAN MAKNA KONOTATIF “CUKUP AKU SAJA YANG WNI” DALAM UNGGAHAN VIDEO SASETYANINGTYAS: KAJIAN SEMIOTIKA - Latifah Dwi Nurhalizah; Vanda Syaidah Adea Putri; Zahra Ardilawati; Sukma Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article, entitled "The Shift in the Connotative Meaning of 'It's Enough for Me to Be an Indonesian Citizen' in Sasetyaningtyas' Video Post: A Semiotic Study," aims to examine the shift in the connotative meaning of a viral phrase on social media and reveal how this meaning develops to form a myth from the perspective of Roland Barthes' semiotics. This research is limited to an analysis of the meaning in Sasetyaningtyas' video containing the phrase. The method used is qualitative descriptive with a listening and note-taking technique, while data analysis is conducted through an analysis of denotative, connotative, and mythical meanings. The results show that denotatively the phrase only refers to citizenship identity, but at the connotative level, its meaning shifts due to the difference between the creator's intention and audience reception, giving rise to interpretations as questionable satire, a contradictory expression, and even a trigger for public criticism. At the mythical level, this phrase develops into an ideological representation related to the construction of nationalism, the concept of the "ideal Indonesian citizen," and the legitimacy of expressing criticism in the digital space. Thus, the meaning in social media can shift.